1991
DOI: 10.1210/endo-129-6-3299
|View full text |Cite
|
Sign up to set email alerts
|

In VivoRegulation of FSH Synthesis by Inhibin and Activin

Abstract: The effect of a single sc injection of the gonadal peptide, recombinant human activin A (rhActivin A), on gonadotropin synthesis and secretion was examined in adult and immature male and female rats and the effect of recombinant human inhibin A (rhInhibin A) was examined in adult male rats. Pituitary FSH beta, LH beta and alpha messenger RNA (mRNA) levels were determined by blot hybridization. Trunk blood was collected to measure serum FSH levels. Treatment with rhInhibin A (100 micrograms/kg) resulted in a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…In accord with many previous reports [10][11][12][13][14] including ours [15], basal FSH secretion was increased by activin A and suppressed by inhibin A. No significant change was observed in 3 mRNA levels accompanying changes in FSH and LH secretion, though f subunit mRNA decreased to approximately half of the initial level when activin A was added, and a slight increase in a mRNA levels caused by both inhibin A and activin A. Bilezikjian et al [7] observed a significant decrease in activin f monomer and dimer production when activin A was added to rat anterior pituitary cells and proposed a local negative feedback by activin of its own production.…”
Section: Discussionsupporting
confidence: 92%
“…In accord with many previous reports [10][11][12][13][14] including ours [15], basal FSH secretion was increased by activin A and suppressed by inhibin A. No significant change was observed in 3 mRNA levels accompanying changes in FSH and LH secretion, though f subunit mRNA decreased to approximately half of the initial level when activin A was added, and a slight increase in a mRNA levels caused by both inhibin A and activin A. Bilezikjian et al [7] observed a significant decrease in activin f monomer and dimer production when activin A was added to rat anterior pituitary cells and proposed a local negative feedback by activin of its own production.…”
Section: Discussionsupporting
confidence: 92%
“…In the pituitary, FSH is stimulated by locally produced activin, and ovarianderived inhibin antagonizes activin (17,42,(45)(46)(47). Inhibin shares its ␤-subunit with activin, and can compete with activin for binding with ActRII/IIB; however, inhibin binding affinity to ActRII/IIB is 2-10ϫ lower than activin binding affinity to ActRII/IIB (6, 8, 48 -50).…”
Section: Discussionmentioning
confidence: 99%
“…A slight increase of inhibin B and FSH were observed in the men. It is known that inhibin B, a dimeric gonadal glycoprotein, inhibits the pituitary secretion of FSH in a classic feedback loop, while secretion from a Sertoli cell is promoted by FSH (11)(12)(13) …”
Section: Discussionmentioning
confidence: 99%
“…However, the influences on inhibin B, FSH and other principal sex hormones and on women subjects were not investigated. Inbihib B is produced by Sertoli cells, provides negative feedback on FSH secretion and is considered to be an importan marker of spermatogenesis (11)(12)(13)(14).…”
mentioning
confidence: 99%